2010
DOI: 10.1111/j.1744-6163.2010.00263.x
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempters in the Emergency Department Before Hospitalization in a Psychiatric Ward

Abstract: It is important to conduct a suicide risk assessment when individuals are admitted to an ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…A population‐based case‐control study found that the number of visits of suicide attempters to emergency departments was associated with future risk of suicide 17 . Indeed, suicide attempters were nearly 12 times more likely to report ongoing suicidal ideation in the emergency department than nonattempters 18 . Predicting risk factors for reattempts of suicide among attempters presenting at emergency departments is therefore critical.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A population‐based case‐control study found that the number of visits of suicide attempters to emergency departments was associated with future risk of suicide 17 . Indeed, suicide attempters were nearly 12 times more likely to report ongoing suicidal ideation in the emergency department than nonattempters 18 . Predicting risk factors for reattempts of suicide among attempters presenting at emergency departments is therefore critical.…”
Section: Introductionmentioning
confidence: 99%
“… 17 Indeed, suicide attempters were nearly 12 times more likely to report ongoing suicidal ideation in the emergency department than nonattempters. 18 Predicting risk factors for reattempts of suicide among attempters presenting at emergency departments is therefore critical.…”
Section: Introductionmentioning
confidence: 99%
“…Emergency physicians come across a myriad of medical afflictions resulting from suicide attempts [ 1 , 2 ]. According to the 2019 WHO report, the age-standardized suicide rate in India is 1.25 per million population, against the global average of 0.9 per million population [ 3 ]. However, it is expected to witness an increase after the decriminalization of suicide in India has addressed under-reporting.…”
Section: Introductionmentioning
confidence: 99%